Rising Profits and Falling Market Share – A Case of National Bank - Mainrai, Girish; Mohania, Sarvesh (Indian Journal of Finance, 2021)
Banks play the role of intermediary by accepting deposits from the depositors and lending the same to the borrowers. The spread between interest given to depositors and received from borrowers is the source of interest income. The income received from all other sources constitutes non-interest for the banks. The present case is related to National Bank, which has over 6,000 branches across pan India that declared its financial results for the financial year 2020 recently. The financial results of National Bank over the years were exhibiting fall in the main source of income, which is the interest income for the bank. This was coupled with a falling market share for the bank. The consultant hired by the top management identified several issues behind this alarming trend like image, processes, products, and services to name a few. The customers perceived National Bank to be slow and lethargic. Similarly, the customers viewed the processes in the bank to be very cumbersome and not customer-friendly. The bank was considered to be a laggard in digital products, lacking the latest features offered by the competitors. The report from the consultant was an eye-opener for the top management, which realized that it had to work on many fronts to reverse the falling interest income trend. National Bank needs to modify its existing products and adopt innovation concerning products, services, and processes. After identifying the grey areas, the top management is now committed to resolving the issues faced by National Bank.